2015
DOI: 10.1080/15567036.2011.555440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Equivalence Ratio and Particle Size on EFB Char Gasification

Abstract: In this study, the effects of equivalence ratio and biochar particle size on high heating value, gas composition, carbon conversion, and gas production from the empty fruit bunch biochar were experimentally investigated in a fluidized bed reactor. Equivalence ratio varied from 0.1 to 0.34, while the size varied from 0.2 mm ≤ s ≥ 1 mm. It was observed that the syngas production increased as the air flow rate increased until equivalence ratio was equivalent to 0.24 and finally decreased with increasing equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…They observed that H2 yield improved using small particles due to the heat transfer resistance was decreased with the small size of biomass [54]. Other studies has looked into the effect of different particles sizes of fruit bunch on the ranges of higher than or equal to 0.2mm and lower than 2mm on producer gas, carbon conversion and high heating value in a fluidized bed at 800 oC, the outcome indicated that the H2 and CO compositions, producer gas yield, high heating value and carbon conversion increased when particles size decreased [55]. It is evidenced through various research and experiments that using smaller particles in the gasification process yields more efficiency [47][48] [49][50] [55].…”
Section: Biomass Particle Sizementioning
confidence: 97%
See 2 more Smart Citations
“…They observed that H2 yield improved using small particles due to the heat transfer resistance was decreased with the small size of biomass [54]. Other studies has looked into the effect of different particles sizes of fruit bunch on the ranges of higher than or equal to 0.2mm and lower than 2mm on producer gas, carbon conversion and high heating value in a fluidized bed at 800 oC, the outcome indicated that the H2 and CO compositions, producer gas yield, high heating value and carbon conversion increased when particles size decreased [55]. It is evidenced through various research and experiments that using smaller particles in the gasification process yields more efficiency [47][48] [49][50] [55].…”
Section: Biomass Particle Sizementioning
confidence: 97%
“…Other studies has looked into the effect of different particles sizes of fruit bunch on the ranges of higher than or equal to 0.2mm and lower than 2mm on producer gas, carbon conversion and high heating value in a fluidized bed at 800 oC, the outcome indicated that the H2 and CO compositions, producer gas yield, high heating value and carbon conversion increased when particles size decreased [55]. It is evidenced through various research and experiments that using smaller particles in the gasification process yields more efficiency [47][48] [49][50] [55]. The main reason is that crushing the particles to smaller sizes, ideally between 1 -5 mm in diameter would in fact offer much higher surface area allowing more efficient mass and heat transfer [47][48] [49][50] [55].…”
Section: Biomass Particle Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Considering an ER of 0.30 for the air co-gasification case, the producer gas yield is expected to be around 4.48 Nm 3 /kg fuel. However, as the amount of gasification agent injected into the reactor increases, the decomposition and reformation of heavier hydrocarbons are favored, and consequently, a greater amount of gas per unit of fuel mass is generated [50]. For the oxygen co-gasification case, there exists an inverse relationship between producer gas LHV and the yield since greater values of the LHV lead to a smaller volume produced of gas per unit of dry fuel fed due to the partial removal of nitrogen from the provided gasification agent.…”
Section: Producer Gas Yieldmentioning
confidence: 99%